AN EVALUATION OF WEB ACCESSIBILITY FOR TOP LEARNING AND DEVELOPMENT COMPANY WEBSITES. - KURANGI, CHINNA RAO (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Nowadays, website becomes very essential in day to day life to communicate information, obtain knowledge, etc. Web accessibility provides access to web resources to various types of persons irrespective of age, language, culture, disability, nationality and so on. The global accessibility of websites is still a greater issue for website developers and researchers. Large number of researches is carried out to evaluate the web accessibility of different websites. In recent days, learning and development company websites are most important website as the learning process starts with these kind of websites. Some of the learning and development companies include Adobe e-learning, Wiley learning, CIPD learning, Lynda, etc. As e-learning technology is very useful for students at various levels, there is a need to evaluate the website for accessibility. This paper provides a study about the accessibility of learning company website homepages. A total 100 learning company websites are investigated under distinct conformance levels of WCAG 2.0 recommendation utilizing automatic accessibility assessment methods to discover accessibility report of websites and then classified them comparatively into three sets namely low accessible websites named MRIII, medium accessible websites called MR-II and high accessible websites called MR-I. In this paper, we have investigated 100 learning and development company websites using three standard web accessibility evaluation tools namely a Checker, WAVE and Cynthia Says tool. This paper proposes the wanted steps which shall be taken to extra improve the accessibility of the websites and using by all.